2013
DOI: 10.4149/gpb_2013003
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical, antioxidant and protective effect of Rhus tripartitum root bark extract against ethanol-induced ulcer in rats

Abstract: Abstract. Rhus tripartitum (sumac) is an Anacardiaceae tree with a wide phytotherapeutic application including the use of its roots in the management of gastric ulcer. In the present study the Rhus tripartitum root barks extract (RTE) was phytochemical studied, in vitro tested for their potential antioxidant activity using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and reducing power assay and in vivo evaluated for its ability to prevent ethanol-induced gastric ulcer in rats. The RTE was rich in phenolics, flavonoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…2004 , 2005 ; Alimi et al. 2013 ) which supports our findings of high-antioxidant property of RTEE. It was found that the sakuranetin content was more in RREE than RTEE.…”
Section: Discussionsupporting
confidence: 90%
“…2004 , 2005 ; Alimi et al. 2013 ) which supports our findings of high-antioxidant property of RTEE. It was found that the sakuranetin content was more in RREE than RTEE.…”
Section: Discussionsupporting
confidence: 90%
“…According to those surveyed for example S. tripartita (Anacardiaceae) known locally as "Djedari", aqueous decoction (67.96%), powder (16.50%) or infusion (15.53%) was considered as the most popular methods of preparation that can address several diseases such as digestive (F C = 66.90%), skin (F C = 11.27%) and circulatory (F C = 10.56%). Concerning the chemical studies of this plant, several compounds such as flavonoids, biflavonoids, isobiflavonoids, catechin, epicatechin-3-O-gallate, proanthocyanidin oligomers and polymers, polysaccharides, condensed tannins have been isolated from different parts of the plant (Tebourbi et al, 2006;Alimi et al, 2013). This plant has been used in Tunisian traditional medicine to treat diarrhoea and dysentery.…”
Section: Discussionmentioning
confidence: 99%
“…Several plant extracts have been shown to have pharmacologic properties with applications to many disease models including EtOH-induced hepatotoxicity [8][9][10]. We have previously shown that treatment of rats with R. tripartita extracts provided a dose-dependent protection against EtOH-induced ulcer [11].…”
Section: Introductionmentioning
confidence: 94%
“…Plant extracts are multicomponent systems, and some have bioactive effects such as hepatoprotective and antioxidant properties in vivo against EtOH-induced toxicity [9,10]. For R. tripatita, we have previously shown that the root bark extract protects over EtOH-induced ulcer in rats, [11] while others demonstrated its antifungal and antibacterial properties [4,6].…”
Section: A C C E P T E Dmentioning
confidence: 99%